A study on the efficacy and safety of a scalp oil-balancing compound acid for scalp seborrheic dermatitis - Songling YAO; Sha LI; Xiaoyan CHEN; qing LIU; Jia WANG; Lina JIN; Ying FENG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the efficacy and safety of a Compound Acid in improving seborrheic dermatitis of the scalp. Methods Fifty patients with seborrheic dermatitis who met the inclusion criteria were enrolled. The subjects underwent scalp brushing with Compound Acid for a total of four brushings, with the first acid brushing on the day of enrollment and subsequent brushings at one-week interval. Symptom scores were assessed before each acid brushing. A follow-up examination was conducted two weeks after the last acid brushing. Clinical signs and symptoms such as papules, greasiness, erythema, and dandruff were scored using skin microscopy. The status of Malassezia infection was detected using fungus fluorescent microscope. A questionnaire was used to evaluate subjects' scalp itching and pain. Results Forty-seven subjects completed this study. Following the use of the Compound Acid, subjects showed significant improvements in maculopapule scores (from 2.09±1.25 to 0.13±0.34), greasiness scores (from 3.19±0.77 to 0.87±0.65), erythema scores (from 3.23±0.63 to 0.43±0.68), and dandruff scores (from 3.26±0.94 to 0.55±0.65) (all P<0.01). In 95.74% of patients, Malassezia was changed from positive to negative. Subjective scores for scalp itching and pain were improved from 3.21±0.75 to 0.57±0.58 and from 1.70±1.27 to 0.50±0.60, respectively (both P<0.01). No adverse reactions were reported throughout the study. Conclusion The compound acid is effective and safe for seborrheic dermatitis, including improvements in scalp itching, maculopapules, greasiness, dandruff and scalp pain.